Stem Cells from Human Exfoliated Deciduous Tooth Exhibit Stromal-Derived Inducing Activity and Lead to Generation of Neural Crest Cells from Human Embryonic Stem Cells - Karbalaie, Khadijeh (Cell J, 2015)
OBJECTIVE: The neural crest is a transient structure of early vertebrate embryos that generates neural crest cells (NCCs). These cells can migrate throughout the body and produce a diverse array of mature tissue types. Due to the ethical and technical problems surrounding the isolation of these early human embryo cells, researchers have focused on in vitro studies to produce NCCs and increase their knowledge of neural crest development. MATERIALS AND METHODS: In this experimental study, we cultured human embryonic stem cells (hESCs) on stromal stem cells from human exfoliated deciduous teeth (SHED) for a two-week period. We used different approaches to characterize these differentiated cells as neural precursor cells (NPCs) and NCCs. RESULTS: In the first co-culture week, hESCs appeared as crater-like structures with marginal rosettes. NPCs derived from these structures expressed the early neural crest marker p75 in addition to numerous other genes associated with neural crest induction such as SNAIL, SLUG, PTX3 and SOX9. Flow cytometry analysis showed 70% of the cells were AP2/P75 positive. Moreover, the cells were able to self-renew, sustain multipotent differentiation potential, and readily form neurospheres in suspension culture. CONCLUSION: SHED, as an adult stem cell with a neural crest origin, has stromal-derived inducing activity (SDIA) and can be used as an NCC inducer from hESCs. These cells provide an invaluable resource to study neural crest differentiation in both normal and disordered human neural crest development.